CHEMICAL COMPOSITION OF 4 STARS IN THE HYADES - Shereta, E. P. (Одеські астрономічні публікації, 2017)
The parameters of atmospheres (Теf, 1оg g, [fе/Н], Vt) of 4 stars of Hyades are certain. Spectrums are got on a spectrograph ELODIE on a 1.93m telescope in the observatory of OHP (France). Overabundances are got 0.1 dех for all investigated elements. .